Jannat: Paradise in Islamic Art Mumtaz Currim, ed. Mumbai: The Marg Foundation, 2012. 144 pages. (American Journal of Islam and Society, 2014)
This rare publication on Islamic art and architecture revolves around a clearconceptual idea. A plethora of broad and specific survey texts continue to bepublished; however, very seldom does a thematic book come along with a thoroughlook at one idea. The collection is composed of an introduction, a port-128 The American Journal of Islamic Social Sciences 31:2folio, and ten essays. As with many compilations, the essays are not all of thesame caliber and there are some structural issues. And yet the whole is a refreshinglook at the theme of jannat (paradise) in Islamic art and architecturein the Indian subcontinent. Not only are several historical eras encompassed,but the important connection to contemporary artistic expressions is also made.Mumtaz Currim’s introduction succinctly discusses the themes covered.His excellent summary of the philosophical and cosmological concepts of paradisein relation to the garden is followed by a clear account of the chaharbagh (quad-partite garden) and the Mughal legacy of gardens as microcosmsof paradise. The relationship of water to both gardens and paradise are reflectedupon with respect to engineering and the expressions in textile art. Thesection concludes with a look at paradise in literary works and popular art.The portfolio includes beautiful reproductions of two very differentgroups of calligraphic art. The first collection is from the twelfth- to sixteenthcenturymanuscript Qur’ans in Hyderabad’s Salar Jung Museum. The selectedverses refer to paradise, such as those found in the chapters of al-Fātiḥah (TheOpening), al-Raḥmān (The Merciful), and al-Wāqi‘ah (The Event). The manuscripts’calligraphy, as well as their geometric and arabesque elaborations,are vividly reproduced in the color images. The second collection consists ofcontemporary artworks by Salwa Rasool, who uses canvas, vellum, leather,and other materials to focus on the Names of Allah and Sūrat al-Fātiḥah’s,chapter and religious phrases. With very little accompanying text, aside fromthe notation of details, the reader is introduced to the concept of paradisethrough the sheer beauty of the Qur’an’s textual descriptions and the word’sevocative role. The juxtaposition of historical and contemporary works revealsthe continuity of the concepts in Islamic cultures ...